2022
DOI: 10.1080/08897077.2021.1944953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Spin in the Abstracts of Systematic Reviews and Meta-Analyses on Cannabis use Disorder

Abstract: Background: Clinicians rely upon abstracts to provide them quick synopses of research findings that may apply to their practice. Spin can exist within these abstracts that distorts or misrepresents the findings. Our goal was to evaluate the level of spin within systematic reviews (SRs) focused on the treatment of cannabis use disorder (CUD). Methods: A systematic search was conducted in May 2020. To meet inclusion criteria, publications had to be either an SR or meta-analysis related to the treatment of cannab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the broader biomedical literature, misreporting and misinterpretation of study findings are evidently common practices that produce spin bias [ 10 , 20 , 21 ]. A comparison of 896 abstracts with their full text conclusions observed that 15–35% were “inconsistent” [ 22 ].…”
Section: Critical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the broader biomedical literature, misreporting and misinterpretation of study findings are evidently common practices that produce spin bias [ 10 , 20 , 21 ]. A comparison of 896 abstracts with their full text conclusions observed that 15–35% were “inconsistent” [ 22 ].…”
Section: Critical Discussionmentioning
confidence: 99%
“…As far as we know, this is the only report on the identification of nonsignificant results and spin bias in the Discussion sections of published articles. Spin bias has been examined between an abstract and the text in randomized controlled trials [ 20 , 22 , 24 , 25 ] and in systematic reviews [ 21 , 26 , 27 ]. Spin bias in abstracts is especially serious because many readers look only at the abstract.…”
Section: Limitationsmentioning
confidence: 99%
“…Study materials, data, and protocols were provided on Open Science Framework to increase transparency and reproducibility of our results 18 . Additionally, our methodology was based from a previous study 21 …”
Section: Methodsmentioning
confidence: 99%
“…Other studies have found at least a 30% prevalence of spin in systematic reviews in the fields of emergency medicine, ophthalmology (especially cataract therapies), addiction medicine (including cannabis use disorder and alcohol use disorder), and physiotherapy (particularly low back pain). [8][9][10][11][12][13] Systematic reviews provide a complete source of evidence-based medicine, as they offer clinicians a comprehensive synthesis of the available findings on a specific treatment. 14 Since researchers collate and analyze many randomized controlled trials for systematic reviews and meta-analyses, these reports are often considered the gold standard for evidence-based medicine and are used to create clinical practice guidelines (CPGs).…”
Section: Ovid Medlinementioning
confidence: 99%
“…The methods described within our study are also described in similar concurrent studies that evaluated systematic reviews for spin and assessed method qualities in their respective fields. [9][10][11][12] We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 18,19 and Murad and Wang's 18,19 guidelines for meta-epidemiological studies to draft this manuscript.…”
Section: Overviewmentioning
confidence: 99%